Annual Plan of Orissa 1978-79 (Draft) - Planning Commission (Planning Commission, 1977)
After twenty are five years of planning and development, Orissa continues to remain as one of the economically backward States, inspite of the fact that it is endowed with fertile land, abundant water, rich mineral deposits and forest resources. the paradox of poverty amidst plenty is no where so remarkably visible as in the case of Orissa. This has been largely due to lack of adequate infrastructure, which resulted in the slow pace of agricultural and industrial development and ultimately slow rate of economic growth. Slow economic growth of the State is noticeable in almost all the sectors of the economy.
Planning and Co-ordination Department, Government of Orissa